IMPLEMENTATION OF TEN STEPS TOWARDS SUCCESSFUL BREASTFEEDING AT TANAH KALIKEDINDING HEALTH CENTER SURABAYA CITY, 2020 - Wahyuni Mahmud Date; Wahyul Anis; Dwiyanti Puspitasari (UNIVERSITAS AIRLANGGA, 2021)
Abstract Background One of the government's efforts to increase the achievement of exclusive breastfeeding is the 10 LMKM program. Since 1991 in Indonesia, it has been introduced, but in its implementation it is not yet known by all health facilities even though several existing steps have been implemented, but the 10 LMKM policy has not been known by providers.Objectives Describe implementation and barriers to providers in program implementation, identify compliance and barriers to mothers as program recipients. Methods The research used descriptive qualitative research. The sampling technique used was purposive sampling to explore the implementation of 10 LMKM in Tanah Kalikedinding Health Center. Informants in accordance with the inclusion criteria 7 providers and 8 mothers as program recipients. Researchers interacted offline and online via video calls while adhering to health protocols. Results The implementation of 10 LMKM has been running with the internal policies of the Puskesmas referring to the Permenkes, carrying out tasks according to the SOP. Several providers have attended training and disseminated it to staff. Monitoring and evaluation is carried out through the credential team at the Puskesmas. Officers in implementing 10 LMKM to support the achievement of exclusive breastfeeding are committed to complying with the SOP. Provider barriers from external factors are the lack of health workers, especially midwives on duty, so that KIE regarding breastfeeding and others is not optimal. Mothers as program recipients when ANC is already in IEC, obediently follow the services provided and have not been fostered or referred to breastfeeding support groups. Barriers to exclusive breastfeeding in program implementation are influenced by external factors of working mothers. Conclusion The implementation of the 10 LMKM program at the Tanah Kalikedinding heath center has not been maximized.